Reinventing Philosophy of Religion - Oppy, G. author. aut Link
VIII, 106 p.
Keywords: Considerations about the existence and nature of God are given far too much weight in contemporary discussions of philosophy of religion. Against prevailing orthodoxy, this introduction to philosophy of religion urges a broader perspective that attends seriously to a wide range of religious and non-religious worldviews.